Roles of Gibberellins and Abscisic Acid in Regulating Germination of Suaeda salsa Dimorphic Seeds Under Salt Stress - Li, Weiqiang; Yamaguchi, Shinjiro; Khan, M. Ajmal; An, Ping; Liu, Xiaojing; Tran, Lam-Son P. (Frontiers in Plant Science, 2016)
Seed heteromorphism observed in many halophytes is an adaptive phenomenon toward high salinity. However, the relationship between heteromorphic seed germination and germination-related hormones under salt stress remains elusive. To gain an insight into this relationship, the roles of gibberellins (GAs) and abscisic acid (ABA) in regulating germination of Suaeda salsa dimorphic brown and black seeds under salinity were elucidated by studying the kinetics of the two hormones during germination of the two seed types with or without salinity treatment. Morphological analysis suggested that brown and black are in different development stage. The content of ABA was higher in dry brown than in black seeds, which gradually decreased after imbibition in water and salt solutions. Salt stress induced ABA accumulation in both germinating seed types, with higher induction effect on black than brown seeds. Black seeds showed lower germination percentage than brown seeds under both water and salt stress, which might be attributed to their higher ABA sensitivity rather than the difference in ABA content between black and brown seeds. Bioactive GA4 and its biosynthetic precursors showed higher levels in brown than in black seeds, whereas deactivated GAs showed higher content in black than brown seeds in dry or in germinating water or salt solutions. High salinity inhibited seed germination through decreasing the levels of GA4 in both seeds, and the inhibited effect of salt stress on GA4 level of black seeds was more profound than that of brown seeds. Taken together higher GA4 content, and lower ABA sensitivity contributed to the higher germination percentage of brown seeds than black seeds in water and salinity; increased ABA content and sensitivity, and decreased GA4 content by salinity were more profound in black than brown seeds, which contributed to lower germination of black seeds than brown seeds in salinity. The differential regulation of ABA and GA homeostases by salt stress in dimorphic seeds might provide a strategy for S. salsa plants to survive adverse environmental conditions.